Odor preferences shape discrimination learning in rats - Lee, Joshua (Behav Neurosci, 2013)
Forced-choice discrimination is a standard behavioral paradigm used to test animals’ abilities in learning and memory. In this type of task, a reward association is made between a sensory stimulus and a food or water reward and the frequency of correct choice for the stimulus associated with the reward is measured. We here show that when olfactory sensory stimuli are used, spontaneous preferences for odors can influence speed of acquisition in a forced-choice discrimination task. We first show that among a battery of 53 odorants, some odorants elicit longer bouts of spontaneous investigation than others. We confirm that these odor preferences are robust and reliable by measuring relative spontaneous investigation times for pairs of simultaneously presented odorants. Finally, we show that performance on a forced-choice olfactory discrimination depends on relative spontaneous preferences between the rewarded and unrewarded odorants. Namely, rats acquire novel forced-choice odor discrimination problems significantly faster if the preferred odorant, as assessed by relative spontaneous investigation time, is associated with the reward. These results indicate that even subtle differences in the tendency for an animal to approach and investigate one odorant over another can lead to substantial biases in basic learning and memory tasks.